Arginine–Glycine Amidinotransferase Deficiency and Functional Characterization of Missense Variants in GATM. Issue 9 (27th June 2016) - DesRoches, Caro‐Lyne; Bruun, Theodora; Wang, Peixiang; Marshall, Christian R.; Mercimek‐Mahmutoglu, Saadet
Abstract : We performed functional characterization of rare missense variants in GATM reported in the Exome Variant Server database. We developed a clinical severity scoring system to assess phenotype and genotype correlation. We cloned a novel GATM transcript and performed site‐directed mutagenesis and GATM activity measurement to functionally characterize missense variants. Seven missense variants with 0% of wild‐type GATM activity indicated putative pathogenicity. ABSTRACT: Arginine–glycine amidinotransferase (GATM) deficiency is an autosomal‐recessive disorder caused by pathogenic variants in GATM . Clinical features include intellectual disability, hypotonia, and myopathy. Due to normal neurodevelopment in asymptomatic individuals on creatine monotherapy, GATM deficiency is a good candidate for newborn screening. To determine the carrier frequency of GATM deficiency, we performed functional characterization of rare missense variants in GATM reported as heterozygous in the Exome Variant Server database. To assess phenotype and genotype correlation, we developed a clinical severity scoring system. Two patients with mild phenotype had a nonsense missense variant. Severe phenotype was present in patients with missense as well as truncating variants. There seems to be no phenotype and genotype correlation. We cloned a novel GATM transcript. We found seven missense variants retaining 0% of wild‐type GATM activity indicating putative pathogenicity. Based on our study results, high Genomic Evolutionary Rate Profiling conservation score, conserved amino acid substitution in species, and low allele frequency in exome databases would be the most sensitive in silico analysis tools to predict pathogenicity of missense variants. We present first study of the functional characterization of missense variants in GATM as well as clinical severity score of patients with GATM deficiency.